Exploring of the suitability of garnets for immobilizing nuclear waste and radiation shielding - Yilmaz, Demet; Kilic, Ayse Didem; Kalecik, Sedanur (Pergamon-Elsevier Science Ltd, 2025)
In this study, the structural, chemical composition and gamma and nuclear shielding properties of some garnets were investigated. The experimental studies were made on the mass attenuation coefficients (MAC), linear attenuation coefficients (LAC), mean free path (MFP), half-value layer (HVL), effective atomic numbers (Zeff) and the radiation protection efficiency (RPE) in the high energy region. The fast neutron removal cross sections (ER), exposure buildup factors (EBF) were theoretically determined. The neutron absorption equivalent dose was measured of the garnet by 241 Am-Be fast neutron source. It may be concluded that P1.21 has better photon shielding than the other samples investigated. The equivalent dose rate absorbed by the P1.21 garnet sample was found to be 36.80 % mu Sv/h and the P1.21 sample shows promise as a neutron shielding option. Also, the detection of inclusion minerals were made by EPMA and SEM analysis. It is observed that P1.21 sample is pyrope, P1.3 sample is andradite and P1.6 sample is grossular series. Also, according to ICP-MS results, it is possible to say that the P1.21 sample, which contains high amount of uranium, thorium, Y and Zr and has a high radiation absorption capacity, is a potential garnet structure for nuclear waste immobilization. Garnet's crystal structure and chemical durability enable safe containment and long-term storage of radioactive elements, facilitating their secure disposal.
Keywords: Garnet; Gamma and neutron shielding; ULEGe detector